2011
DOI: 10.1371/journal.pone.0016709
|View full text |Cite
|
Sign up to set email alerts
|

BCG Vaccination: A Role for Vitamin D?

Abstract: BackgroundBCG vaccination is administered in infancy in most countries with the aim of providing protection against tuberculosis. There is increasing interest in the role of vitamin D in immunity to tuberculosis. This study objective was to determine if there was an association between circulating 25(OH)D concentrations and BCG vaccination status and cytokine responses following BCG vaccination in infants.MethodsBlood samples were collected from UK infants who were vaccinated with BCG at 3 (n = 47) and 12 (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…Therefore, we were interested in the recently suggested role of vitamin D and its active metabolite 1,25(OH) 2 D 3 in modulating immune responses [11,45,46]. Specific cell types involved in the immune response express the enzyme CYP27B1, which produces 1,25(OH) 2 D 3 in situ [47].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we were interested in the recently suggested role of vitamin D and its active metabolite 1,25(OH) 2 D 3 in modulating immune responses [11,45,46]. Specific cell types involved in the immune response express the enzyme CYP27B1, which produces 1,25(OH) 2 D 3 in situ [47].…”
Section: Discussionmentioning
confidence: 99%
“…. The authors suggested vitamin D may play an immunomodulatory role in the immune response to BCG vaccine [63]. As discussed earlier, vitamin D inhibits IFN-γ producing Th1 cells.…”
Section: Impact Of Vitamin D On Immune Response To Vaccinesmentioning
confidence: 99%
“…These vaccines were demonstrated to enhance humoral and cellular immune responses, activate the inflammatory action of macrophages, and increase IFN-γ-producing cells. Furthermore, BCG-vaccinated infants are almost six times as likely to have sufficient vitamin D concentrations three months after receiving the BCG vaccine compared with unvaccinated infants, and this association remains strong even after adjusting for season, ethnic group, and sex [111]. In the vaccinated group, there is also a strong inverse correlation between the IFN-γ response to M. tuberculosis PPD and vitamin D concentration (i.e., infants with higher vitamin D concentrations have lower IFN-γ responses).…”
Section: The Non-genomic Role Of Vitamin D In Malariamentioning
confidence: 98%